Enterococcus avium bed-sore infection: A rara avis - Jangla, Sunayana Mukesh (Indian Journal of Case Reports, 2024)
Enterococci are Gram-positive cocci that are normal inhabitants of the urogenital and intestinal tracts of human beings and animals. Of the pathogenic species of Enterococci, Enterococcus avium is an infrequent cause of human infections. This report is an atypical case of bed-sore infection caused by E. avium in an elderly male with multiple comorbidities. Although the patient was given antibiotics along with surgical debridement, he passed away. This case calls attention to the pathogenic prospect of E. avium in clinical settings.